Leading Virtual Teams – A Literature Review - Zeuge, Anna; Oschinsky, Frederike; Weigel, Andreas; Schlechtinger, Michael; Niehaves, Björn (2020)
ABSTRACT With the outbreak of COVID-19, many organizations are facing the challenge of switching to virtual work. A large number of teams suddenly need to work no longer physically but digitally together. However, switching to virtual teamwork is not only a special requirement for the team, but also for the leadership of virtual teams. Despite great efforts to explore virtual leadership, research still lacks an overview of the leadership of virtual teams. We address this gap by presenting the results of a narrative literature review conducted by five independent scientists to map the broadest possible spectrum of results with special attention to a heterogeneity of the results. Thereby, our work provides a point of departure for a structured exploration of virtual team leadership. Keywords virtual teams, leadership, management, emotional intelligence, communication ABOUT THE AUTHOR/S Anna Zeuge University of Siegen anna.zeuge@uni-siegen.de Anna Zeuge works as a research assistant at the Chair of Information Systems, University of Siegen, also being a member of the local institute of interdisciplinary research. After her studies in business administration (B. Sc.) she completed her master degree (Controlling and Risk Management M. Sc.) at the University of Siegen. Her main field of research is teamwork and collaborative work in a digital environment. Additionally, she is interested in and working on work-life-balance and autonomy. Frederike Oschinsky University of Siegen frederike.oschinsky@uni-siegen.de Andreas Weigel University of Siegen andreas.weigel@uni-siegen.de Michael Schlechtinger University of Siegen michael.schlechtinger@uni-siegen.de Björn Niehaves University of Siegen bjoern.niehaves@uni-siegen.de New Future of Work 2020, August 3–5, 2020 © 2020 Copyright held by the owner/author(s).